1981
DOI: 10.1073/pnas.78.11.7166
|View full text |Cite
|
Sign up to set email alerts
|

Movement of antibody-coated latex beads attached to the spirochete Leptospira interrogans.

Abstract: Antibody-coated latex beads (Ab-beads) were attached to Leptospira interrogans serovars iMini 3055 and icterohaemorrhagiae SC1157. The movement of the Ab-beads relative to the motion of the cells was observed by direct darkfield microscopy or was recorded on videotape. When the Ab-beads were attached to the front end of motile cells, the Ab-beads were displaced towards the back end of the cells. When the cells reversed direction, the Ab-beads also reversed direction. A number of hypotheses were proposed and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 22 publications
(16 reference statements)
4
35
0
Order By: Relevance
“…4). These motions are reminiscent of the movement of antibody-coated latex beads attached to members of the Leptospiraceae (14,16,22) and indicate that protrusions have a fluid surface. They are also consistent with the notion that PFs are surrounded by an outer membrane sheath.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4). These motions are reminiscent of the movement of antibody-coated latex beads attached to members of the Leptospiraceae (14,16,22) and indicate that protrusions have a fluid surface. They are also consistent with the notion that PFs are surrounded by an outer membrane sheath.…”
Section: Discussionmentioning
confidence: 98%
“…To estimate the frequency of cell protrusions, we examined 30 cells by dark-field microscopy at several time points during a growth curve and determined the fraction of cells with protrusions at one or both ends. In certain instances, methylcellulose was added to the medium (4,16,24).…”
Section: Methodsmentioning
confidence: 99%
“…A relatively recent observation shows that lateral "qntramembrane" movement occurs at remarkably rapid rates. Charon et al [25] have shown that the movement of a molecule within the plasma membrane can occur within the substance of the membrane at the rate of 10-14 microns per second. The degree of fluidity demonstrated by the experiments of these authors needs to be regarded as a general property of biological membranes, provided that they possess the appropriate kinds of phospholipids.…”
Section: Why Is a Route Through The Substance Of The Ameloblast Consimentioning
confidence: 99%
“…Cell motions were slow enough not to be confused with stroboscopic effects. Because these cells are immobilized by strong blue light (18,27,28), observations were made at low-light intensities, usually using a yellow-green filter.…”
Section: Methodsmentioning
confidence: 99%